Faktor Terjadinya Keterlambatan Waktu bongkar muat Kontainer MV. Oriental Jade di Pelabuhan Manokwari - Hidayatullah, Mohammad Faizal; Moh. Zaenal Arifin; Latifa Ika Sari (Jurnal Navigsi Maritim, 2024)
The purpose of this study is to determine the factors causing delays in loading and unloading time of MV Oriental Jade at Manokwari Port, the impact of delays in loading and unloading time of MV containers. Oriental Jade at Manokwari Port and efforts in order to overcome the late loading and unloading time of containers on MV. Oriental Jade at Manokwari Port. This research uses a qualitative case study method, with data analysis techniques using Fishbone diagrams. The research was conducted on a container ship named MV. Oriental Jade in 2022. The data collection techniques used are observation, interviews, and documentation studies related to efforts to overcome the causes of delays in loading and unloading time of MV Oriental Jade. The interview involved Captain, chief officer and foreman. The results of this study indicate that the factors causing delays in the loading and unloading time of MV Oriental Jade at Manokwari Port are due to the limitations of loading and unloading equipment, namely the cranes available at Manokwari Port are fixed cranes, these cranes do not have wheels so that they hinder the loading and unloading process, other factors because loading and unloading workers often arrive late to the loading and unloading location besides that heavy rain is a factor that hinders container loading and unloading time because for the safety of loading and unloading workers. This has an impact on the delay of the MV Oriental Jade container unloading process at Manokwari Port being delayed, and ship operational losses such as port rental costs. Therefore, the effort made is that the ship communicates with the port to determine the schedule and activities of loading and unloading containers so that the container loading and unloading process runs smoothly.